Transformation of the Role of Internal Auditors in Oversight of Financial Management and Fraud Prevention - Sugianto, Yanie; Sugiyanto, Sugiyanto; Tatariyanto, Firman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the transformation of the role of internal auditors (APIP) in overseeing financial management and preventing fraud within the FOLU Net Sink 2030 Program of the Ministry of Forestry, a results-based climate financing initiative. Using a qualitative case study approach, the research explores how internal auditors adapt from traditional compliance-oriented functions toward more strategic and consultative roles as trusted advisors. Data were collected through in-depth semi-structured interviews with internal auditors and relevant officials, supported by document analysis and qualitative data processing using NVivo. The findings indicate that, although internal auditors conceptually understand their oversight mandate in the FOLU and Results-Based Contribution (RBC) framework, fraud prevention practices remain largely focused on administrative controls and post-factum verification. Structural constraints, including limited data interoperability, restricted access to donor information, and the absence of explicit regulatory mandates for APIP oversight of climate-related grants, constrain the effectiveness of preventive fraud control. The study further reveals that the transformation of the internal audit role is gradual, evolutionary, and highly influenced by program dynamics rather than formal regulation. Internal auditors have begun to perform advisory, risk warning, and accompaniment functions for implementing units; however, capabilities in digital fraud detection and technical verification of Measurement, Reporting, and Verification (MRV) are still developing. Conceptually, the study contributes an “APIP Assurance–Advisory Continuum” model and introduces the notion of a “Digital-Governance Enabler,” highlighting the importance of data integration, multidisciplinary competence, and digital adaptation in strengthening oversight of climate finance programs. These findings underscore the need for regulatory reform, risk-based auditing, and enhanced digital governance to improve fraud prevention and accountability in results-based environmental programs.